1988
DOI: 10.1037/0278-7393.14.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Word identification in reading proceeds from spelling to sound to meaning.

Abstract: Van Orden (1987) reported that false positive errors in a categorization task are elevated for homophonic foils (e.g., HARE for A PART OF THE HUMAN BODY). Two new experiments replicate this finding and extend it to nonword homophone foils (e.g., SUTE FOR AN ARTICLE OF CLOTHING). False positive errors to nonword homophone foils substantially exceed false positive errors to nonhomophonic nonword spelling controls, showing that the phonological characteristics of the nonword foils are critical. Because nonwords a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
347
3
6

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(399 citation statements)
references
References 42 publications
43
347
3
6
Order By: Relevance
“…When probed with a target word related to the inappropriate form (e.g., CALM) subjects are slower to reject the target word as being unrelated to the overall meaning of the homophone sentence (e.g., He had lots of patients) as opposed to a nonhomophone control sentence (e.g., He had lots of students). This result is consistent with that of van Orden (1987;van Orden, Johnston, & Hale, 1988) using similar stimuli. Gernsbacher and Faust (1991a) also found that people who were skilled at story comprehension were more efficient at suppressing inappropriate forms of homophones than were less-skilled comprehenders.…”
Section: Methodssupporting
confidence: 82%
“…When probed with a target word related to the inappropriate form (e.g., CALM) subjects are slower to reject the target word as being unrelated to the overall meaning of the homophone sentence (e.g., He had lots of patients) as opposed to a nonhomophone control sentence (e.g., He had lots of students). This result is consistent with that of van Orden (1987;van Orden, Johnston, & Hale, 1988) using similar stimuli. Gernsbacher and Faust (1991a) also found that people who were skilled at story comprehension were more efficient at suppressing inappropriate forms of homophones than were less-skilled comprehenders.…”
Section: Methodssupporting
confidence: 82%
“…The most probable reason is that the presentation of a word results automatically (and unavoidably) in some form ofphonological processing. This is more consistent with models of reading that place derivation of a phonological representation as the primary process in reading (see, e.g., Lukatela & Turvey, 1994a, 1994bVan Orden, 1987Van Orden, Johnston, & Hale, 1988;Van Orden, Pennington, & Stone, 1990). These phonological mediation models propose that on an initial encounter with a printed letter string, a prelexical phonological code is created, and that this is compared with representations within a phonological lexicon.…”
Section: Why Was the Aoa Effect Not Eliminated In Experiments 2-5?supporting
confidence: 57%
“…For example, many models of word processing [e.g., Patterson and Shewell, 1987] propose that reading and listening have separate input systems, but both input systems may then propagate information to a shared language processing system [also Coltheart et al, 1994;Lukatela and Turvey, 1994;Perfetti et al, 1992;Van Orden et al, 1988]. Similarly, according to Geschwind's [1979] description of word comprehension, both reading and listening involve a common pathway through Wernicke's area, but reading also involves a preceding pathway through additional temporo-parietal areas that transform the visual form of the word to its corresponding auditory form.…”
Section: Introductionmentioning
confidence: 99%